(untitled) (Journal of Forest and Natural Resource Management, 2025)
Urbanization in Nepal is rapidly altering the structure and ecological function of remnant forest patches, many of which continue to support wide range of biodiversity. Banpale Forest is small patch in Pokhara city amidst the urbanization. The forest is being used for recreational purpose for daily physical exercise, picnics and bird watching. The forest patch refuges several bird diversities however bird database is scattered and lacks recent bird diversity studies. Thus, bird study was conducted from 2022 to 2024. Bird count was carried out each moth along a transect line. Bird database was compiled from the data of this study and reported in the former literatures. Species richness, migratory status, feeding guilds, and conservation status were assessed from the collected data. The study resulted a total of 147 bird species in a Banpale Forest, representing 16 orders. Passeriformes were the most sighted bird group accounting 82 species. The forest refuges resident (116 species), winter visitors (25 species) and summer visitors (6 species). Insectivores are the abundant among the bird composition (70 species). The forest refuges 28 CITES listed birds; five are globally threatened while nine nationally threatened species. The study revealed Banpale Forest supports high bird diversity inferring as the critical refugia in the rapidly urbanizing and bustling Pokhara city. Thus, the study emphasized and initiate protection of the urban forest patches in the city, securing habitat of birds and natural beauty.